PENGARUH SOCIAL MEDIA ENGAGEMENT TERHADAP REPUTASI PT KERETA API INDONESIA - Nayla Salsabila Hanidah; Razie Razak; Slamet Parsono (Indonesian Journal of Digital Public Relations (IJDPR), 2022)
The reputation of a company is a valuable intangible asset, but it is becoming more difficult to manage due to rapid digital expansion. Today, social media is an important part of establishing a company's reputation. The researcher analyzes if corporate social media is advantageous to businesses in this report. Researchers examined public participation on social media in the depiction of a company's reputation in a survey of 100 PT Kereta Api Indonesia customers who follow Instagram @keretaapikita. The findings suggest that the level of public participation in social media has a beneficial impact on the perception of a company's reputation. These findings' implications are explored as a reference in the use of social media to establish a company's reputation.